2014
DOI: 10.1007/s11033-014-3459-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel haplotype within C-reactive protein gene influences CRP levels and coronary heart disease risk in Northwest Indians

Abstract: According to several epidemiological and clinical studies, the concentration of C-reactive protein (CRP) in blood is associated with the risk of coronary heart disease (CHD). However, these studies are limited in high incidence and prevalence area of North-West India. The present case control study investigated the contribution of three relevant CRP single nucleotide polymorphisms: -717A>G located in the promoter region (rs2794521), +1059G>C on exon2 (rs1800947) and +1444C>T in the 3' UTR (rs1130864) in 180 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In this study, we investigated whether polymorphisms rs2794521 of the CRP gene, rs1800796 of the IL6 gene and rs1799964 of the TNF gene are related to elevated blood glucose among the Thai population. Regarding the results, the distribution of each variant was consistent with previous studies [9,12,15,[19][20]. The wild type of each of the selected gene polymorphisms was most frequent, followed by the heterozygous variant, and nally the homozygous variant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we investigated whether polymorphisms rs2794521 of the CRP gene, rs1800796 of the IL6 gene and rs1799964 of the TNF gene are related to elevated blood glucose among the Thai population. Regarding the results, the distribution of each variant was consistent with previous studies [9,12,15,[19][20]. The wild type of each of the selected gene polymorphisms was most frequent, followed by the heterozygous variant, and nally the homozygous variant.…”
Section: Discussionsupporting
confidence: 90%
“…Polymorphisms located in promoter regions, including rs2794521 (-717 A/G) of CRP gene, -572 C/G (rs1800796) of IL6 gene and -1031 T/C (rs1799964) of TNF gene, have been associated with T2DM risk [7,[9][10][11][12][13]. Several studies demonstrated a notable in uence of the rs2794521 polymorphism on CRP secretion [14][15][16]. Alteration of CRP concentration may modify T2DM risk [5][6]9].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that increased inflammatory cytokine levels and inflammatory cytokine activity detectable in peripheral blood have a prognostic role in predicting future cardiac events and clinical course (Tousoulis et al, 2006;De Gennaro et al, 2012). Recent studies have also shown that inflammationrelated genes might be correlated with CAD risk (Zakynthinos and Pappa, 2009;Shankar and Kakkar 2010;Li et al, 2012;Xie et al, 2012;Singh et al, 2014), thus aligning a number of inflammatory cytokines, their expression and their activity, as key mediators of CAD. Inflammatory pathways are mediated by proximal cytokines, such as Tumor Necrosis Factor-Alpha (TNF-α) and Tumour Necrosis Factor Beta (TNF-β)/Lymphotoxin Alpha) (LT-α), Interferon gamma (IFN-ɣ) and interleukin-6 (IL-6) which suggest they may influence CAD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CRP-717 T/C polymorphism is related to the development of acute and chronic inflammatory processes 6,7,11 , few studies have evaluated this genetic polymorphism in infectious processes 8,9,12 . In Hepatitis B virus (HBV) infection, CRP-717 T/C polymorphism evaluation has been restricted to the Asian population 8,9 .…”
Section: Introductionmentioning
confidence: 99%